Compensatory plasticity: time matters - Lazzouni, Latifa; Lepore, Franco (Frontiers in Human Neuroscience, 2014)
Plasticity in the human and animal brain is the rule, the base for development, and the way to deal effectively with the environment for making the most efficient use of all the senses. When the brain is deprived of one sensory modality, plasticity becomes compensatory: the exception that invalidates the general loss hypothesis giving the opportunity of effective change. Sensory deprivation comes with massive alterations in brain structure and function, behavioural outcomes, and neural interactions. Blind individuals do as good as the sighted and even more, show superior abilities in auditory, tactile and olfactory processing. This behavioural enhancement is accompanied with changes in occipital cortex function, where visual areas at different levels become responsive to non-visual information. The intact senses are in general used more efficiently in the blind but are also used more exclusively. New findings are disentangling these two aspects of compensatory plasticity. What is due to visual deprivation and what is dependent on the extended use of spared modalities? The latter seems to contribute highly to compensatory changes in the congenitally blind. Short term deprivation through the use of blindfolds shows that cortical excitability of the visual cortex is likely to show rapid modulatory changes after few minutes of light deprivation and therefore changes are possible in adulthood. However, reorganization remains more pronounced in the congenitally blind. Cortico-cortical pathways between visual areas and the areas of preserved sensory modalities are inhibited in the presence of vision, but are unmasked after loss of vision or blindfolding as a mechanism likely to drive cross-modal information to the deafferented visual cortex. Plasticity in the blind is also accompanied with neurochemical and morphological changes; both intrinsic connectivity and functional coupling at rest are altered but are likewise dependent on different sensory experience and training.